Distribusi Zakat Dalam Upaya Memberdayakan Ekonomi Kaum Dhuafa Di Baznas Kota Jambi (Studi Kasus Kelurahan Binaan Ulu Gedong) - Salma salma; Titin Agustin Nengsih; G W I Awal Habibah (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The seriousness of Islam in building partiality for the poor can be seen from the word of Allah in several verses of the Qur'an. The National Amil Zakat Agency or often called BAZNAS is an official institution whose job is to collect and distribute funds to help the Muslim community, especially the poor. This study aims to determine the process of distributing zakat at Baznas in Jambi City, the obstacles encountered, and the efforts made in the distribution of zakat by BAZNAS Jambi City. This research approach uses a qualitative approach based on the philosophy of postpositivism. Data was collected using interviews and field observations. The results showed that the process of distributing zakat funds was carried out with several considerations, namely the accuracy of zakat distribution, program socialization about the BAZNAS program, adjusting program objectives, and monitoring recipients of zakat funds. The obstacles faced in the distribution are the non-linear education of officers, the difficulty in finding human resources who are honest, trustworthy, siddiq, responsible, fair, and willing to help, amil zakat does not understand the fiqh of zakat, the community does not understand the benefits and functions of zakat, as well as the official website of BAZAS The city of Jambi has not been fully utilized. Efforts are being made to educate amil and muzakki, assign program responsibilities, conduct human resource selection and evaluation, conduct deliberations for consensus, socialize job responsibilities and policies, improve program services, and conduct reviews and meetings to discuss problems.